TEOLOGI KRISTEN DALAM PERSPEKTIF PENGINJILAN PAULUS SEBAGAI UPAYA PEMAKNAAN INJIL DAN PEMBANGUNAN JEMAAT DI TENGAH TANTANGAN KONTEKS SOSIAL BUDAYA - Gusti Rara; Agnes Patiung; Ireni Tandililing; Asniaty Patintingan; Kevin Stefanus Purba (Adisam Publisher, 2025)
This article examines Christian theology from the perspective of Paul's evangelism as an effort to interpret the Gospel and build congregations amidst the challenges of the socio-cultural context. This study uses a qualitative approach with library research methods, examining New Testament texts, especially Paul's letters, as well as contemporary theological and missiological literature in Indonesian. The results of the study indicate that Paul's evangelism emphasizes the integration of fidelity to the core of the Gospel, the transformation of congregational life, sound teaching, and harmonious community relations. Paul's contextual and inculturative evangelism strategy is relevant for the church today, as it allows for the delivery of the Gospel that is sensitive to the culture and needs of the congregation without compromising theological truth. Congregational development through teaching and community relations demonstrates that evangelism is not only doctrinal, but also practical and relational, forming a strong Christian character and an inclusive community. This study provides theoretical and practical contributions to the modern church in developing relevant evangelism strategies and building strong congregations in a pluralistic and dynamic society.